Case Report: Longitudinal Extensive Transverse Myelitis With Novel Autoantibodies Following Two Rounds of Pembrolizumab - Charabi, Salma; Engell-Noerregaard, Lotte; Nilsson, Anna Christine; Stenör, Christian (Frontiers in Neurology, 2021)
A 63-year-old male with metastatic non-small cell lung cancer developed longitudinal extensive transverse myelitis (LETM) following two cycles of Pembrolizumab, an immune checkpoint inhibitor (ICI) targeting the programmed cell death receptor 1 (PD-1). Magnetic Resonance Imaging (MRI) showed centromedullary contrast enhancement at several levels, cerebrospinal fluid (CSF) cytology showed lymphocytic pleocytosis, and indirect immunofluorescence assay (IFA) on primate cerebellum, pancreas and intestine revealed strong binding of neuronal autoantibodies to unknown antigens. CSF C-X-C motif ligand 13 (CXCL13) was elevated. The patient was treated with plasma exchange (PEX), intravenous (i.v.) methylprednisolone (MP) 1 g/day for 5 days followed by oral (p.o.) MP 100 mg/day for 10 days with clinical and radiological response. However, after discontinuation of MP, LETM relapsed and the patient developed paralytic ileus presumably due to autoimmune enteropathy and suffered a fatal gastrointestinal sepsis. Findings of novel neuronal autoantibodies and highly elevated CXCL13 in CSF suggest that the severe neurological immune related adverse event (nirAE) was B-cell mediated contrary to the commonly assumed ICI induced T-cell toxicity. Individual evaluation of the underlying pathophysiology behind rare nirAEs is essential for choosing treatment regimens and securing optimal outcome.